2012
DOI: 10.1136/bmj.e3533
|View full text |Cite
|
Sign up to set email alerts
|

The effect of folic acid based homocysteine lowering on cardiovascular events in people with kidney disease: systematic review and meta-analysis

Abstract: Objective To systematically review the effect of folic acid based homocysteine lowering on cardiovascular outcomes in people with kidney disease.Design Systematic review and meta-analysis.Data sources Medline, Embase, the Cochrane Library, and ClinicalTrials.gov to June 2011.Study selection Randomised trials in people with non-dialysis dependent chronic kidney disease or end stage kidney disease or with a functioning kidney transplant reporting at least 100 patient years of follow-up and assessing the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 48 publications
(69 reference statements)
4
46
1
2
Order By: Relevance
“…Neither treatment reduced composite CVD outcome, allcause mortality, or dialysisdependent kidney failure despite significant reduction in homocysteine level [120] . These results are supported by a recent review which concluded that folic acid based homocysteine lowering does not reduce CV events in people with kidney disease and therefore folic acid based regimens should not be used for the prevention of CV events in people with hyperhomocysteinaemia and kidney disease [121] .…”
Section: Homocysteinesupporting
confidence: 72%
“…Neither treatment reduced composite CVD outcome, allcause mortality, or dialysisdependent kidney failure despite significant reduction in homocysteine level [120] . These results are supported by a recent review which concluded that folic acid based homocysteine lowering does not reduce CV events in people with kidney disease and therefore folic acid based regimens should not be used for the prevention of CV events in people with hyperhomocysteinaemia and kidney disease [121] .…”
Section: Homocysteinesupporting
confidence: 72%
“…Studies showed that in the general population, a 25% lower homocysteine level is associated with a 11% lower risk of coronary artery disease and a 19% lower risk of stroke (34,35). Furthermore, Veeranna et al showed that adding homocysteine levels to the Framingham risk score enhances the prediction of risk in individuals at intermediate CVD risk (36).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the disappointing results of intervention trials aimed at curbing the high mortality in CKD-5D patients [18,21,22], renal physicians should increase efforts to test biologically sound interventions that may attenuate the enormous cardiovascular and noncardiovascular risk differential between patients with kidney failure and the general population. In this respect, the hypothesis proposed by Huang et al [20] would certainly be worth testing.…”
Section: Saturated Fats and Human Healthmentioning
confidence: 99%